Sosialisasi Undang-Undang ITE Serta Pelatihan E-Learning bagi Guru-Guru Sekolah Menengah Negeri 17 Bungo, Dusun Renah Sungai Ipuh, Kecamatan Limbur Lubuk Mengkuang - Burhanuddin; Zulkifli; Syahwami; Poiran; Hamirul; Ariyanto; M, Hasdani; Darmawanto (HIMPUNAN DOSEN GEMILANG INDONESIA, 2023)
Conventional learning methods are mostly dominated by abstract concepts so that they can make understanding of the subject matter less than optimal. However, there are actually some learning materials that are suitable for using conventional methods and some are more suitable for using learning with the application of E-learning. Apart from that, the rapid development of technology has unwittingly changed various forms of interaction in people's social lives.